Heterobranch Sea Slugs s.l. (Mollusca, Gastropoda) from the Southern Ocean: Biodiversity and Taxonomy - Manuel Ballesteros; Alex Hopkins; Miquel Salicrú; Matt J. Nimbs (Diversity)
The Southern Ocean, located between Antarctica and the southern tips of South America, Africa and Australia, encompasses an immense area across the southern Atlantic, Pacific and Indian oceans with no clearly defined limits. For the purposes of studying marine heterobranch sea slugs, we consider the Southern Ocean to include all ocean areas located south of latitude 41° S. South of this latitude, we consider different areas and zones: the area of South America (the Patagonia/Magellanic area), the island of Tasmania, the southern island of New Zealand, the Subantarctic area (the Falkland Islands, South Georgia Island, the South Orkney Islands, South Sandwich Island, Bouvet Island, the islands of Crozet and Prince Edward, the Kerguelen Islands, and Macquarie Island) and the area of Antarctica, in which we consider four zones (Weddell Sea, West Antarctica, Ross Sea and East Antarctica). Reviewing all available references and unpublished data from the authors, in total, 394 species of heterobranch sea slugs have been recorded to date in the Southern Ocean > 41° S, with Nudibranchia standing out with 209 species and Cephalaspidea with 90 species. The marine heterobranchs of Tasmania (154 species) and southern New Zealand (120 species) have been well studied. Sea slug fauna of the Antarctic and Subantarctic regions have been the subject of several partial studies; however, there are still many gaps in knowledge across both areas. Eighty-nine different species of sea slug have been recorded so far in strictly Antarctic waters (West Antarctica, 45 species; Weddell Sea, 48 species; Ross Sea, 51 species; East Antarctica, 42 species), while in the various Subantarctic regions, there are 93 species (36 species from South Georgia, 17 species from the South Orkneys, 12 species from south Sandwich, 6 species from Bouvet, 10 species from Prince Edward and Crozet Islands, 15 species from Kerguelen, 3 species from Macquarie Island, 29 species from the Falkland Islands and 71 species from the coast of South America). In the taxonomic section, for each of the species, the location and the authors of the records are indicated, and for many of the species, interesting biological, taxonomic or biogeographic observations are also provided. The importance of sampling in underexplored areas is discussed, as well as greater-depth sampling for a better understanding of the sea slugs of the Southern Ocean.